Effect of Rice Bran Incorporation on the Texture Profile and Physicochemical Properties of Fresh Pasta (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Rice bran (RB) contains significant amounts of nutrients. RB's nutritious and low price makes it highly interesting to be added to food formulation. The study aims to investigate the effect of the addition of edible RB to the fresh pasta (Fettuccine). Four RB levels (5%, 10%, 15%, and 20%) were chosen to substitute durum semolina content in the fresh pasta formulations. The results indicate that the addition of RB increased the darkness and redness of the pasta. The texture of the pasta was influenced by the addition of RB where increased hardness, adhesiveness, gumminess, and chewiness were observed as the amount of RB increased, while the cohesiveness and resilience showed a decreased trend. Results showed a decrease in carbohydrate (49-59%), while an increase in crude protein (9.63-10.16%), crude fiber (0.31-2.64%), crude fat (0.01-4.99%), and ash (0.77–2.06%) of the pasta. In conclusion, the use of RB to replace durum wheat semolina altered the cooking quality, improved some nutritional composition, and obtained high acceptability of RB fresh pasta.
Keywords: Rice bran; Fettuccine; Fiber; Fresh pasta; Durum semolina